Chiral lanthanide complexes: coordination chemistry, spectroscopy, and catalysis. - Bennett, S; Core, B; Blake, M; Pope, S; Mountford, P; Ward, B (Royal Society of Chemistry, 2014)
The coordination chemistry and catalytic applications of organometallic and related lanthanide complexes bearing chiral oxazoline ligands is an area that has been largely underdeveloped, in comparison to complexes based upon lanthanide triflates for use in Lewis acid catalysis. In this article we report on the coordination chemistry of the bis(oxazolinylphenyl)amide (BOPA) ligand with lanthanide alkyl and amide co-ligands (Ln = Y, La, Pr, Nd, Sm). Their structural and spectroscopic characterisation are reported, including an assessment of their photophysical properties using luminescence spectroscopy, and are supported by density functional calculations. The application of these complexes in the hydroamination/cyclisation of aminoalkenes, and in the ring-opening polymerisation of rac-lactide is reported.